2019
DOI: 10.1007/s10490-018-9608-6
|View full text |Cite
|
Sign up to set email alerts
|

Family firms and internationalization in the Asia-Pacific: the need for multi-level perspectives

Abstract: We address the challenges in understanding how family ownership shapes international business across institutional contexts in and beyond the Asia-Pacific, a region with diverse and often contradictory approaches to internationalization and family firms. We begin by introducing the topic and summarizing the papers in the special issue. We then develop a multi-level framework for understanding internationalization of family firms consisting of individual/family, family firm and institutional levels. We emphasiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 58 publications
(71 reference statements)
0
28
0
Order By: Relevance
“…Second, we begin a dialogue between two important and growing literature streams: SME internationalization (Knight & Liesch, 2016;Laufs & Schwens, 2014;Lu & Beamish, 2001;McDougall & Oviatt, 1996) and FF internationalization (Arregle et al, 2017;Carney et al, 2015;Duran et al, 2017Duran et al, , 2019Eddleston et al, 2019aEddleston et al, , 2019bGedajlovic, Carney, Chrisman, & Kellermanns, 2012). In bringing these together, we draw on insights from the traditional IB literature, which primarily deals with non-SME/non-FFs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we begin a dialogue between two important and growing literature streams: SME internationalization (Knight & Liesch, 2016;Laufs & Schwens, 2014;Lu & Beamish, 2001;McDougall & Oviatt, 1996) and FF internationalization (Arregle et al, 2017;Carney et al, 2015;Duran et al, 2017Duran et al, , 2019Eddleston et al, 2019aEddleston et al, , 2019bGedajlovic, Carney, Chrisman, & Kellermanns, 2012). In bringing these together, we draw on insights from the traditional IB literature, which primarily deals with non-SME/non-FFs.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, high-quality products are influenced by the country-of-origin cues that embody symbolic values and influence customer choice. Eddleston et al (2020) and Eddleston et al (2019) also found that FFs selling high-quality products abroad benefit from professionalization practices that allow them to overcome bifurcation bias. Coherently, De Massis, Audretsch et al (2018) in their study of FFs in the German Mittelstand found that these firms adopt a niche-focused globalization strategy: they are especially proactive in recognizing and exploiting global opportunities, helping keep their product portfolio focused and their resource requirements “controllable” while reducing market risk and increasing revenue.…”
Section: The Evolution Of Ff Internationalization Research: a 30-yearmentioning
confidence: 96%
“…Second, research on internationalization decisions has ignored the related process, hence not providing “process-based explanations, explanations of post-entry outcomes, and explanations involving tension and conflict among family firm actors” ( Reuber, 2016 : 1272). Third, research has overlooked the specific sources of competitive advantages that FFs might leverage when internationalizing, which might emerge from the business model they adopt ( Hennart et al, 2019 ), but also from the specificity of the context ( Eddleston et al, 2020 ; Eddleston et al, 2019 ). Coherently with these trajectories and the growth of this literature stream, research questions addressed in this wave are more variegated, including “How do family aspects influence FF internationalization?”, “How does FF internationalization unfold over time?” , and “What makes FF internationalization unique?”.…”
Section: The Evolution Of Ff Internationalization Research: a 30-yearmentioning
confidence: 99%
See 2 more Smart Citations